Can "natural" flavorings enhance the flavor of low-fat ground beef? - C.F. Carmack; Melvin C. Hunt; Donald H. Kropf; J.R. Schwenke; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1993)
Natural flavorings were evaluated for use in low-fat ground beef, which frequently lacks flavor intensity. Three lean sources, A-maturity (young), E-maturity (mature cow), and imported (cow) beef round muscles, were used to formulate 7% and 25% fat ground beef. A-maturity fat was added to adjust fat levels. Controls (no added flavors) were prepared for each lean source. No additives were used in 25% fat controls, but 7% fat controls contained water (10%), carrageenan (.5%), and encapsulated salt (.38%). Four "natural" flavorings; Dried Cream Extract (DCE, Cumberland Packing Co., Inc.); Natural Prime Beef Base WONF #224545 and #224546 (224545, 224546, Tastemaker); and Hydrolyzed Vegetable Protein (HVP, A.C. Legg, Inc.) were added to 7% fat ground beef at recommended levels. A- and E-maturity domestic 25% fat controls were scored higher (P<.05) for ground beef flavor intensity and lower (P<.05) for off-flavors than 25% fat patties from imported beef. The 7% fat patties from imported lean had greater (P<.05) beef flavor intensity and reduced off-flavors (P<.05) when flavorings 224545, 224546, and HVP were added. These flavorings also enhanced the beef flavor intensity of low-fat patties from A-maturity lean to a level similar to that of the 25% fat control. Beef flavor intensity after a 60-min holding period was not enhanced by the natural flavorings, except when 224546 was added to E-maturity domestic lean. Therefore, the "natural" flavorings were most beneficial with imported lean.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Low-fat; Ground beef; Flavor; Juiciness; Lean source